ANALYSIS OF COMPLIMENT AND ITS RESPONSE IN MOVIE MANUSCRIPT: BRATZ AND FUNNY PEOPLE (PRAGMATIC APPROACH) - PARLI, PARLI (2010)
This research discusses the expression of compliment and response which occured in English movie manuscripts. The objectives of the research are to identify the forms of compliment and respose expression, to examine the intention of compliment, and to describe the types of compliment and response which occured in English movie manuscripts. This research is a descriptive and qualitative type. The data are expressions taken from English movie manuscripts. The source of data is the movie manuscripts entitled Bratz and Funny People. The writer uses observation and document methods to collect the data, while the techniques of data analysis refers to: grammatical analysis for identifying the forms, speech acts theory for examining the intention of compliment and response, and refers to Herbert's classification of compliments for describing the types of compliments and response. Having analyzed the data, the writer founds that the forms of compliments expressions are in declarative sentence, imperative sentence and exclamatory sentence. Related to the intention, the writer identified six kinds of intentions of compliments: to praise, to insult, to motivate, to thanks, to inform, and to tease. There are nine types of compliments and response: appreciation token, comment acceptance-single, praise upgrade, return, scale down, question, disagreement, no acknowledgment, and request interpretation.